Acetazolamide in prevention of acute mountain sickness: a double-blind controlled cross-over study. Issue 6295 (26th September 1981) - Greene, M K; Kerr, A M; McIntosh, I B; Prescott, R J
Abstract : Twenty-four amateur climbers took part in a double-blind controlled cross-over trial of acetazolamide versus placebo for the prevention of acute mountain sickness. They climbed Kilimanjaro (5895 m) and Mt Kenya (5186 m) in three weeks with five rest days between ascents. The severity of acute mountain sickness was gauged by a score derived from symptoms recorded daily by each subject. On kilimanjaro those taking acetazolamide reached a higher altitude (11 v 4 reached the summit) and had a lower symptom score than those taking placebo (mean 4.8 v 14.3). Those who had taken acetazolamide on Kilimanjaro maintained their low symptom scores while taking placebo on Mt Kenya (mean score 1.9), whereas those who had taken placebo on Kilimanjaro experienced a pronounced improvement when they took acetazolamide on Mt Kenya (mean score 2.5). Acute mountain sickness prevented one subject for completing either ascent. Acetazolamide was acceptable to 23 of the 24 subjects. Acetazolamide is recommended as an acceptable and effective prophylactic for acute mountain sickness.